Interrogating International Environmental Law’s Approach to Nature: An Arctic Indigenous Model? - Payva Almonte, Marlene (Journal of Northern Studies, 2025)
International Environmental Law (IEL) reflects a rooted misconception of nature present across the international legal system, whereby nature is presented as instrumental to satisfying human needs oriented to unlimited economic growth. Such an anthropocentric view lacks an ecological awareness that conceives and values nature in its own right, and fails to recognize humans as part of it, leading to relentless exploitation of the natural world, at the core of the climate and ecological crises. In this article, I contend that rethinking IEL in a way to interrogate its inherent conceptual premises and embrace non-Western views on and relationalities with nature is essential. The Arctic being at the forefront of climate effects that severely and disproportionally impact its ecosystems and (human and non-human) communities; and “sustainable development” projects contextualised as part of the green transition pose additional risks to the region. I argue that Indigenous knowledge from Arctic peoples can contribute to expanding IEL’s conceptual horizons and correcting inherited (mis-)understanding of nature and reimagining the human–nature relationship. Integrating, for example, the overarching principle of respect of the Skolt Sami in ordinary human–nature relationships can assist in rethinking IEL and inform a truly sustainable design, interpretation and implementation of its provisions.